REVIEW: Journalists’ voices explore dangerous times - Philip Cass (Asia Pacific Network, 2016)
Review of: Reporting from the Danger Zone: Frontline journalists, their jobs and an increasingly perilous future, by Maria Armoudian. New York and Abingdon: Routledge, 2017, 155pp. ISBN 978-1-138-84005-8.